The determinants of mutual fund performance: Evidence from the Vietnamese market - Nguyen, Van Nam (2018)
The purpose of this study is to evaluate performance of mutual funds in Vietnamese market and examine which factors affect fund performance. The sample comprises of 72 equity mutual funds in Vietnamese market from 2009 to 2017. The fund performance is estimated from Single-Index model (Jensen, 1968) and Four-factor model (Carhart, 1997). The dissertation employs a panel data regression (fixed effects model) to examine the impact of fund size, fund age, net cash flows, past performance on fund performance. Overall, mutual funds in Vietnam do not show superior performance. Only 8 funds significantly outperform the VN Index. The results from panel data regression suggest that Size, Net cash flows, Past performance are significantly correlated with fund performance in whole fund sample and foreign funds. For domestic funds, only net cash flows have a clear impact on performance. For comparison purpose, VN100 Index is used as a benchmark to measure risk-adjusted performance. The VN100 Index benchmark improves fund performance at individual level. In addition, Size, Net cash flows and Past performance still demonstrate significant correlation with fund performance. The results of the comparison postulate that fund performance is sensitive to the selection of benchmark and determinants have explanatory power.